LYOTROPIC LIQUID CRYSTALLINE SYSTEM FOR EFFECTIVE TOPICAL DELIVERY OF TOLNAFTATE - Mahajan, Jyotsna T; Gujarathi, Nayan; Jadhav, Anil; Pathan, Vasim; Borse, Lakshmikant (Asian Journal of Pharmaceutical Research and Development, 2018)
The present investigation deals with the formulation, optimization and evaluation of liquid crystalline cream of Tolnaftate. Brij-78 used as a surfactant, Cetostearyl alcohol was used as a co-surfactant and Silicon oil as a oil phase. Liquid crystalline cream system, has a potential for efficient delivery of Tolnaftate (1%), as topical dermal drug delivery system. The liquid crystalline system enhance the diffusion of water insoluble drug Tolnaftate through the skin for effective result. Liquid crystals (LC) are substances that flow like liquids but maintain some of the ordered structure characteristics of crystalline solids. Based on the ways that LCs are generated, they can be classified into two types 1) Thermotropic LCS and 2) Lyotropic LCs. Incorporation of the drug in liquid crystal increased its antimycotic activity against different antifungal microorganisms. Used surfactant enhance the penetration of drug and also improve the solubility of drug. The objective of this study was to increase the diffusion coefficient of drug through the formulation, and also to improve the availability of drug at the site of action. The prepared liquid crystalline cream exhibited the expected, viscosity, drug content, pH, spreadability, in vitro drug release and in vitro antimycotic inhibitory activity. Liquid crystalline cream for tolnaftate was found to be stable cream. It was found to have better in vitrorelease profile characteristics, and in vitro antimycotic activity, it can be concluded that the formulation F5 has better potential of antimicrobial activity and to enhance the diffusion of drug through the cream.